Konflik Peran ganda Dan Dukungan Suami Hubungannya Dengan Kesejahetraan Subjektif Polwan Yang Sudah Menikah - Pesta Gresela Sitorus; Anizar Rahayu; Nugaan Yulia Wardhani (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study is a quantitative study that aims to determine the relationship between work-familyconflict and the husband's support for the subjective well-being of married female police officers. Thevariables in this study were subjective well-being, work-family conflict, and husband's support. The subjectsinvolved in this study were married policewomen who served in Polres X with a population of 130 people,while the sampling technique used a saturated sampling technique, which used the entire population.Researchers used 3 scales as a measuring tool, namely: subjective well-being scalework-family conflict scale,and husband's support scale. The results of this study indicate that there is a significant negative relationshipbetween work-family conflict and subjective well-being with r = - 0.732 and P = 0.000 (p <0.05). There is asignificant positive relationship between husband's support and subjective well-being with r = 0.744 and p =0.000 < 0.005. Furthermore, there is a significant relationship between work-family conflict and husband'ssupport together with subjective well-being of R Square (R2) = 0.653 and p = 0.000 <0.05. The contributionof work-family conflict and husband's support to subjective well-being is 65.3%.